The Implementation of Green Accounting in Indonesia: A Case Study - Dunakhir, Samirah; Idrus, Mukhammad; Afiah, Nur (Yayasan Gema Bina Nusantara, 2024)
This research aims to analyze the application of green accounting at one of the state-owned enterprises in Indonesia. Green accounting is a concept that systematically integrates objects, transactions, or social events (humans) and environmental events (earth) to produce complete and useful accounting information. This presents a challenge for companies that utilize their profits to cover capital and costs but fail to allocate costs for environmental management and corporate social responsibility. We used documentation as the data collection method, with interviews serving as supporting data. The study employed a qualitative descriptive research approach, utilizing the content data analysis method. We can conclude that PT XYZ Indonesia has met some of the accounting standards based on the results of the five steps in implementing green accounting: identification, recognition, measurement, presentation, and disclosure of costs related to environmental management activities. However, certain stages of implementing green accounting, specifically the identification and disclosure of accounting policies, did not adhere to the existing standards. The urgency of this research lies in providing information about the application of green accounting, which can enhance companies' ability to mitigate environmental issues. The findings of this research will contribute to the development of knowledge and insight regarding green accounting. This is in accordance with one of Indonesia's national research priorities or focus areas, which is the green economy.